2012
DOI: 10.1186/1749-7922-7-26
|View full text |Cite
|
Sign up to set email alerts
|

Late evaluation of the relationship between morphological and functional renal changes and hypertension after non-operative treatment of high-grade renal injuries

Abstract: ObjectiveTo evaluate the anatomical and functional renal alterations and the association with post-traumatic arterial hypertension.MethodsThe studied population included patients who sustained high grades renal injury (grades III to V) successfully non-operative management after staging by computed tomography over a 16-year period. Beyond the review of medical records, these patients were invited to the following protocol: clinical and laboratory evaluation, abdominal computed tomography, magnetic resonance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
1
8
0
2
Order By: Relevance
“…Hypertension is defined as having a systolic blood pressure (SBP) of ≥140 mmHg and a diastolic blood pressure (DBP) of ≥90 mmHg (≥140/≥90 mmHg; Tabassum and Ahmad, 2011 ). Every 20/10 (SBP/DBP) mmHg increase indicates a higher risk stage of hypertension; stage 1 (140–159/90–99 mmHg), stage 2 (≥160/≥100 mmHg; Archer, 2000 ; Weber et al, 2014 ) with the latter stage requiring immediate medical attention (Weber et al, 2014 ). Importantly, the American Society of Hypertension and ISH recommend that individuals with blood pressure of 120–139/80–89 mmHg be considered as pre-hypertensives (Weber et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypertension is defined as having a systolic blood pressure (SBP) of ≥140 mmHg and a diastolic blood pressure (DBP) of ≥90 mmHg (≥140/≥90 mmHg; Tabassum and Ahmad, 2011 ). Every 20/10 (SBP/DBP) mmHg increase indicates a higher risk stage of hypertension; stage 1 (140–159/90–99 mmHg), stage 2 (≥160/≥100 mmHg; Archer, 2000 ; Weber et al, 2014 ) with the latter stage requiring immediate medical attention (Weber et al, 2014 ). Importantly, the American Society of Hypertension and ISH recommend that individuals with blood pressure of 120–139/80–89 mmHg be considered as pre-hypertensives (Weber et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the American Society of Hypertension and ISH recommend that individuals with blood pressure of 120–139/80–89 mmHg be considered as pre-hypertensives (Weber et al, 2014 ). For targeted therapeutic interest, it is essential to realize that pre-hypertensive individuals are three times more likely to succumb to hypertension at a later stage of life than their normotensive counterparts (Archer, 2000 ). It is important to note that according to the Eighth Joint National Committee, it is recommended that for the general population, pharmacologic treatment be started at an SBP of 150 mmHg or DBP of 90 mmHg.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal failure was not only associated with contrast medium injection but also with interventional procedures. 12 , 13 This study showed no significant differences in the level of creatinine or blood urea nitrogen estimated in patients before and after RAE. Renal failure was found in 1 patient with contralateral kidney hydronephrosis and in 1 patient with abnormal renal function before the intervention.…”
Section: Discussionmentioning
confidence: 59%
“…The presence of preexisting hypertension in adult renal trauma patients is a potential confounder, making it difficult to accurately identify patients with hypertension directly related to the traumatic event. In one study where 9 of 31 patients experienced post-trauma hypertension 80% had a positive family history of arterial hypertension [10]. In contrast, pediatric populations generally do not have pre-existing hypertension, which allows for a potentially more accurate depiction of the association between renal trauma and hypertension.…”
Section: Discussionmentioning
confidence: 97%